Enrichment and impoverishment in agrarian world: Northeast and Southeast Brazil, 19th Century - da Costa, Dora Isabel Paiva [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2019)
This article revisit the classical theme of economic decline of Northeast region of Brazil in nineteenth century and it aims to analyze in comparative perspective the economic performance of the Southeast region. The objective is to identify impacts on agrarian social groups of slave and non-slave owners in the context of economic decline and growth. The main sources are the post-mortem inventories, population´s census and the methodology used is the serial one.
Enriquecimento e empobrecimento no mundo agrário: Nordeste e Sudeste do Brasil, século XIX
Keywords: Decline and Economic Growth; Nineteenth Century; Regional Economic History